PENGGUNAAN ALAT BUKTI ELEKTRONIK DALAM PROSES PERADILAN PERDATA - Gresia Wulaning Rum (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
The development of information technology has brought significant changes to the process of evidence presentation in civil litigation. Electronic evidence, such as emails, instant messages, and digital documents, is now legally recognized as evidence with the same probative value as physical documents. This study analyzes the position of electronic evidence in Indonesian civil procedural law, identifies its advantages and disadvantages, and discusses the challenges faced in its implementation. Based on Law No. 11 of 2008 on Electronic Information and Transactions and its amendment through Law No. 19 of 2016, electronic evidence has been incorporated into the evidentiary system in courts, enabling the use of various digital formats in trials. However, the main challenges include the authentication of evidence, the risk of data manipulation, the admissibility of evidence depending on regulations, and the costs of managing electronic evidence. This study concludes that while electronic evidence plays an important role in the modernization of civil litigation, its success heavily depends on clear regulations and the enhancement of the judiciary’s capacity to effectively manage digital evidence.